2022
DOI: 10.1097/md.0000000000029710
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a prognostic signature for lung adenocarcinoma by integration of 7 pyroptosis-related genes and cross-validation between the TCGA and GEO cohorts: A comprehensive bioinformatics analysis

Abstract: Pyroptosis-related genes (PRGs) have been reported to be associated with prognosis of lung adenocarcinoma (LUAD). Until now, the relationship of PRGs to the prognosis of LUAD patients and its underlying mechanisms have been poorly elucidated. Using The Cancer Genome Atlas (TCGA) LUAD cohort, a prior bioinformatics analysis constructed a prognostic signature incorporating 5 PRGs (NLRP7, NLRP1, NLRP2, NOD1, and CASP6) for predicting prognosis of LUAD patients. However, it has not been validated by the Gene Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Furthermore, a multi-omics analysis by Chen et al revealed that NLRP1 levels were increased in CHOL and LIHC compared to normal tissues [38]. Several additional multi-omics analyses exploring pyroptosisrelated genes in lung adenocarcinoma consistently showed downregulation of NLRP1 in LUAD tissues compared to normal tissues [39][40][41][42]. Consistent with previous studies, our ndings highlight the tumorsuppressive in uence of NLRP1 in the majority of TCGA cancer types.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, a multi-omics analysis by Chen et al revealed that NLRP1 levels were increased in CHOL and LIHC compared to normal tissues [38]. Several additional multi-omics analyses exploring pyroptosisrelated genes in lung adenocarcinoma consistently showed downregulation of NLRP1 in LUAD tissues compared to normal tissues [39][40][41][42]. Consistent with previous studies, our ndings highlight the tumorsuppressive in uence of NLRP1 in the majority of TCGA cancer types.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the downregulation of NLRP1 is correlated with unfavorable DFS in CHOL. Several studies have explored the potential of NLRP1 as a prognostic biomarker in various cancers, including lung adenocarcinoma [39,40,44], gastric cancer [45], prostate cancer [43], pancreatic cancer [46,47], head and neck squamous cell carcinoma [48], and laryngeal carcinoma [49]. Shen et al con rmed that decreased expression of NLRP1 was signi cantly associated with a poor prognosis of LUAD [41].…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that RS strongly predicts outcomes in LUAD patients with various clinical characteristics, particularly in early LUAD patients ( Figures 7A–F ). In order to demonstrate the predictive performance of our model, we compared it with other models based on the TCGA-LUAD database, such as the published gene prediction models of Duan et al (2021) , Zhang et al (2022) , Yang et al (2022) , Xu and Chen, (2021) , Gong et al (2022) . Our model has the greatest c-index of nomogram compared to previously published lung cancer models, as indicated by the findings.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the authors hypothesised that NLRP2 could suppress other types of cancer through affecting NF-κB activity [76]. Furthermore, NLRP2 has been suggested as a potential biomarker for predicting overall survival by building different risk models in patients with head and neck squamous cell carcinoma, pancreatic, lung adenocarcinoma and glioblastoma [80][81][82][83][84][85][86]. NLRP2 can also be used as a marker of leukaemia and has a critical influence on the prognosis after stem cell transplantation [87,88].…”
Section: Nlrp2 In Cancermentioning
confidence: 99%